A CULTURA DIGITAL DA BASE NACIONAL COMUM CURRICULAR E SUA RELAÇÃO COM A EDUCOMUNICAÇÃO NO CONTEXTO DO ENSINO BRASILEIRO - Silva, Joseane Maria Vieira da (2022)
The present research has as its theme the Digital Culture of the National Common Curricular Base (2018) and its relationship with Educommunication in the context of Brazilian Education. The question that led this work was: how does the BNCC's Digital Culture include educommunication practices for its implementation? In this investigative context, Educommunication (a practice that integrates education and communication) and the BNCC Digital Culture (Competency number 5) stand out. The general objective was to analyze the relationship between the BNCC's Digital Culture and Educommunication in the context of Brazilian Education and specifically, in three articles, we sought to: address the process of building the BNCC from contexts parallel to Educommunication; describe the insertions of Educommunication and Digital Culture in the BNCC; and justify the inclusion of Educommunication practices in the curriculum policy for teacher training (BNCC implementers). In the light of the understandings of chosen authors such as Citelli (2011), Soares (2016-2018) and Amestoy et al (2021) we sought to elucidate the topic. The present study was built in a historical period for humanity from 2020 to 2021, in view of the biggest pandemic peak in recent years, SARS-CoV-2. The construction process emerges in the midst of discussions around the implementation of the BNCC. The research is qualitative in nature and the research method is exploratory with bibliographic and documental review, based on concepts of fundamental authors on Educommunication and BNCC. The electronic databases used in the research were: SciELO, Google Scholar and BDTD. Bardin's (2006) content analysis was used, a reference to this type of technique, as the process of theoretical-practical reflection on works and documents such as books, dissertations, theses, articles in electronic journals, national legislation is very didactic. The study identified different forces of external policies that sought to guarantee their educational projects, however, they did not promote practical vectors for the implementation of the new BNCC. The theme was deepened with the proposal to include Educommunication in the continuing education of teachers, as it can contribute to the innovation of teaching and qualification of teaching practice in the implementation of the National Base. The obstacles faced in the pedagogical routine (pandemic) highlighted the lack of teacher training that should include more educommunication practices, manipulation of materials and technologies in education. Given the above, it is concluded that there is a lack of understanding and investment in the relationship between Digital Culture of the BNCC and Educommunication, this is an important concept that needs to appear more in the BNCC because it involves education and communication, two fundamental concepts for the development of a country.